Strategi Percepatan Implementasi Srikandi di Kementerian Perindustrian Untuk Kearsipan Digital Pemerintahan Modern - Rizki Hendriarti; Asropi (PT. Alahyan Publisher Sukabumi, 2026)
The implementation of the Electronic-Based Government System (SPBE) has become a strategic necessity in realizing an effective, transparent, and accountable bureaucracy. One of its supporting instruments is the SRIKANDI application (Integrated Dynamic Archival Information System), a national platform for managing electronic dynamic records. This paper aims to analyze the supporting and inhibiting factors, as well as to formulate strategies to accelerate the implementation of SRIKANDI within the Ministry of Industry of the Republic of Indonesia. The method used is descriptive qualitative research with secondary data analysis through audit document review. The analysis refers to Van Meter and Van Horn’s policy implementation model and Kotter’s organizational change theory. The findings show that SRIKANDI implementation has been carried out at the central level, but has not been evenly applied across all regional work units. The main obstacles include limited network infrastructure, low employee understanding of information technology, and the continued use of internal intranet systems and unofficial communication media in official correspondence. Meanwhile, the supporting factors include a strong legal basis through Presidential Regulation No. 95 of 2018 and leadership commitment to digital transformation. This acceleration is expected to optimize reliable digital records governance and support the realization of digital government in Indonesia.